Changes in paediatric hospital ENT service utilisation following the implementation of a mobile, indigenous health screening service. (October 2013) - Smith, Anthony C; Armfield, Nigel R; Wu, Wei-I; Brown, Cecil A; Mickan, Brooke; Perry, Chris
In 2009, we established a mobile ear-screening service for children in a remote community approximately 350 km north-west of Brisbane. We compared pre-implementation health service utilisation data (2006-2008) with data for the following three years. The study included only children in schools that had participated in screening since the start of the screening programme and for which data for the 6-year study period were available. In the baseline period there were 329 ear, nose and throat (ENT) outpatient appointments at the Royal Children's Hospital (RCH) in Brisbane for children from the selected catchment area. Of these, 166 (51%) were failure-to-attends (FTAs). In the following three years, there were 105 appointments, of which 40 (38%) were FTAs. In the baseline period, 100 children received surgical procedures at the RCH; in the following three years there were 43. In the three years following implementation, 136 children were booked to receive surgical procedures locally at the Cherbourg hospital, and 117 (86%) were completed. Since no other major health service changes occurred in the region during the study period, we conclude that the telemedicine-enabled screening service improved access to specialist care in the community and resulted in fewer outpatient and surgical appointments at the tertiary centre in Brisbane.